2013
DOI: 10.1073/pnas.1312508110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dendritic spines in the mouse auditory cortex during memory formation and memory recall

Abstract: Long-lasting changes in synaptic connections induced by relevant experiences are believed to represent the physical correlate of memories. Here, we combined chronic in vivo two-photon imaging of dendritic spines with auditory-cued classical conditioning to test if the formation of a fear memory is associated with structural changes of synapses in the mouse auditory cortex. We find that paired conditioning and unpaired conditioning induce a transient increase in spine formation or spine elimination, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 50 publications
5
110
0
Order By: Relevance
“…Repeated administration of DA-releasing psychostimulant drugs produces both transient and long-lasting changes in the size and density of dendritic spines on these GABAergic neurons (Dumitriu et al, 2012;Kolb, 1997, 1999;Shen et al, 2009). These dendritic spines may be locations of memory storage in the brain (Lamprecht and LeDoux, 2004); various behavioral experiences have been shown to increase spine formation in vivo (Holtmaat et al, 2005(Holtmaat et al, , 2006Lai et al, 2012;Moczulska et al, 2013;Mu帽oz-Cuevas et al, 2013). Importantly, by comparing the effects of intra-VTA and systemic injections of amphetamine, we recently found that spine plasticity maps onto the accrual of associative drug conditioning rather than the induction of nonassociative drug sensitization (Singer et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Repeated administration of DA-releasing psychostimulant drugs produces both transient and long-lasting changes in the size and density of dendritic spines on these GABAergic neurons (Dumitriu et al, 2012;Kolb, 1997, 1999;Shen et al, 2009). These dendritic spines may be locations of memory storage in the brain (Lamprecht and LeDoux, 2004); various behavioral experiences have been shown to increase spine formation in vivo (Holtmaat et al, 2005(Holtmaat et al, , 2006Lai et al, 2012;Moczulska et al, 2013;Mu帽oz-Cuevas et al, 2013). Importantly, by comparing the effects of intra-VTA and systemic injections of amphetamine, we recently found that spine plasticity maps onto the accrual of associative drug conditioning rather than the induction of nonassociative drug sensitization (Singer et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Hebbian mechanisms have correlates in synaptic structural plasticity, in which LTP is correlated with the formation of new spines [71,72], and LTD is associated with the loss of pre-existing spines [73]. The in vivo upregulation of spine dynamics has been observed following sensory deprivation in somatosensory cortex [74 -77], olfactory cortex [78,79], auditory cortex [80] and visual cortex [74,77,81 -83], and following learning in motor cortex [84][85][86] where the memory of the learned motor task depends on the newly formed synapses [87].…”
Section: Similarities Across Brain Regions In Vivomentioning
confidence: 99%
“…Thus, there are structural correlates of LTP and LTD, which can be assessed with imaging methods. Importantly, also chronic imaging in transgenic mice during a behavioral task showed that transient increases in spine formation rates are correlated with learning [6,12]. Major findings from a study investigating the impact of auditory cued fear conditioning on spine dynamics in the .…”
Section: Mechanisms Of Changementioning
confidence: 99%